PUBLIC USE FOR PRIVATE INTEREST: THE PARADIGM SHIFT ON LAND ACQUISITION FOR NATIONAL STRATEGIC PROJECTS IN INDONESIA - Khairina, Ghassani Irsia; Hantoro, Bimo Fajar; Azzahro, Fathimah; Tirtousada, Dwi; Khoirunnisa, Anandyta Nur (Proceeding ICMA-SURE; Part 1 Proceeding The 8th International Conference on Multidisciplinary Approaches for Sustainable Rural Development, 2026)
Despite their aim to accelerate national development, Indonesia's National Strategic Projects (NSPs) have created a complex landscape of conflict, particularly in land acquisition. The enactment of the Job Creation Law catalyzed the statutorization of NSPs, significantly amending Law Number 2 of 2012 on Land Acquisition for Public Use. This normative research, employing statutory and conceptual approaches, analyses how this new NSP regulation affects the land acquisition paradigm. Major findings reveal a significant paradigm shift, not just in procedure, but in legal-conceptual understanding of public interest itself. The broad definitions and urgent implementation mandates for NSPs now facilitate accelerated land acquisition processes that effectively subordinate community rights in favor of private investment. This shift has profound implications, including an increased susceptibility to expropriation claims, diminished public participation, and a clear re-prioritization of economic growth over social equity. The research concludes that while NSPs are crucial for development, their current framework reinterprets public use to serve private interest, mitigate disproportionate private benefit, and prevent the erosion of communal welfare and legal certainty.